Impact of SARS-CoV-2 on pancreas transplant activity: survey of international surgeons (Br J Surg, 2020)
This study has identified the need for clear and consistent national or international guidelines to be in place in the event of future pandemics to ensure a standardised level of care for all pancreas transplant patients.